Karakteristik dan Visualisasi Aliran Dua Fasa pada Pipa Spiral - Damawidjaya Biksono (Institute of Research and Community Outreach, Petra Christian University, 2006)
The flow of air-water mixtures has been investigated in a horizontal spiral pipe. The effect of flow in the spiral pipe will be used to identify the location bubble transition. The purpose of present study is to understand characteristics of the air - water mixture flow in a horizontal spiral pipe. Measurements of pressure losses and bubble distribution of cross section spiral pipe were carried out for air-water by means of manometer and digital video, respectively. As a result, it is shown that the friction of air-water mixture is greater than that of water, and a location of bubble flow can be identified. Abstract in Bahasa Indonesia : Penelitian aliran udara-air di dalam pipa spiral horizontal telah dilakukan. Efek aliran di dalam pipa spiral dipakai untuk melihat letak lokasi perubahan gelembung udara. Tujuan dari studi ini adalah untuk menjelaskan karakteristik aliran campuran udara-air yang mengalir di dalam pipa spiral horizontal. Pengukuran kerugian tekanan dan letak lokasi penyebaran gelembung udara-air pada penampang melintang pipa, masing-masing menggunakan manometer dan digital video. Hasil koefisien gesek campuran udara-air lebih besar dibandingkan koefisien gesek pada air dan letak posisi aliran udara dapat dijelaskan. Kata kunci: Aliran dua fasa, pipa spiral.